Los fake news. caso: Paro nacional, Babahoyo 2019. análisis de su influencia en los estudiantes de la Carrera de Comunicación Social - Moreta Verdezoto, Juan Carlos (2020)
The research focuses on showing the fackes news, which occurred on the days of National Paro in Ecuador. At the same time we will show what was the influence and level of knowledge that the students of the Social Communication Career of the Technical University of Babahoyo have on this subject. Eighth-semester students have been selected for this. This project will be carried out through the qualitative method, through a focus group and an interview, questions were used to then give way to the interpretation of the information obtained. Likewise, this research is linked to Citizen Participation and Popular Power, a subline of research of the Social Communication career. In recent years the Internet has become one of the largest sources of information, but this has generated great consequences in the veracity of the news, today, all Internet users have the ease of creating or sharing a news quickly, either through social media, or through the web. Many of these people spread messages massively without knowing how truthful this event is.